Global e-commerce Impacts of National Environment and Policy - Kraemer, Kenneth L.; Dedrick, Jason; Melville, Nigel P.; Zhu, Kevin (Cambridge University Press, 2006)
Are the Internet and e-commerce truly revolutionizing business practice? This book explodes the transformation myth by demonstrating that the Internet and e-commerce are in fact being adapted by firms to reinforce their existing relationships with customers, suppliers, and business partners. Detailed case studies of eight countries show that, rather than creating a borderless global economy, e-commerce strongly reflects existing local patterns of commerce, business, and consumer preference, and its impact therefore varies greatly by country. Paradoxically, while e-commerce is increasing the efficiency, effectiveness, and competitiveness of firms, it is also increasing the complexity of their environments as they have to deal with more business partners and also face greater competition from other firms. This incisive analysis of the diffusion and impact of e-business provides academic researchers, graduates, and MBA students with a solid basis for understanding its likely evolution.